Charming the hearts of men [videorecording (DVD)] - DeRose, S. E.; Friel, Anna, 1976-; Astin, Sean; Grammer, Kelsey, 1955-; Ladd, Diane; Gains, Courtney, 1965- (Gravitas Ventures, 2021)
In the early '60s, a sophisticated woman returns to her southern hometown and finds her options are limited. With the help of a Congressional ally, she inspires historic legislation that allows opportunities never before afforded to women.